9(7-3x-4x)+8(5x+7)=27

Simple and best practice solution for 9(7-3x-4x)+8(5x+7)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(7-3x-4x)+8(5x+7)=27 equation:


Simplifying
9(7 + -3x + -4x) + 8(5x + 7) = 27

Combine like terms: -3x + -4x = -7x
9(7 + -7x) + 8(5x + 7) = 27
(7 * 9 + -7x * 9) + 8(5x + 7) = 27
(63 + -63x) + 8(5x + 7) = 27

Reorder the terms:
63 + -63x + 8(7 + 5x) = 27
63 + -63x + (7 * 8 + 5x * 8) = 27
63 + -63x + (56 + 40x) = 27

Reorder the terms:
63 + 56 + -63x + 40x = 27

Combine like terms: 63 + 56 = 119
119 + -63x + 40x = 27

Combine like terms: -63x + 40x = -23x
119 + -23x = 27

Solving
119 + -23x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-119' to each side of the equation.
119 + -119 + -23x = 27 + -119

Combine like terms: 119 + -119 = 0
0 + -23x = 27 + -119
-23x = 27 + -119

Combine like terms: 27 + -119 = -92
-23x = -92

Divide each side by '-23'.
x = 4

Simplifying
x = 4

See similar equations:

| -27=3(1+2x)3 | | 2(n+4)=5(4-n) | | 6(2c+1)=10 | | 4(m-12)=24 | | 2/3d=27 | | 8=6-14 | | 3.4(x-4.5)=2.7 | | 10m^2-35=65n | | X/3--9=13 | | 2(6-7x)=2x-4 | | -6x-16=(x-2)+11x | | 90=3n+20 | | (x+8)-(4x+18)-3x=34(x+7)-(78+57x) | | 2-x/2=1 | | 3x^4-14x^3-49x^2+15x-105= | | -4+8y=42 | | 0.4x-2=x+0.04 | | -14-8z=14-8z | | -3[c]=-15 | | (-2,7)m=2/3 | | 15-x=45+5x | | 4x^2=800 | | -3(t-2)=36 | | 5y+x=42 | | -2x+(7x-24)-2x+y=-129 | | 405x^4-5x^2= | | 4(5+x)=2(6+3x) | | y-7x=30 | | 4p+6q=22 | | 14=9-(x+2) | | 625+x=7 | | 6x-42y+172z=19 |

Equations solver categories